Readiness and Challenges of Implementing Virtual Reality in School Administration: A Case Study at Yayasan Pendidikan YIMI Gresik - Sundari, Sri; Etiyasningsih, Etiyasningsih; Zulinarh, Ariel Teta; Sagiokta, Wahyu Ivana (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
Little is known about the application of Virtual Reality (VR) in school administration, particularly in Indonesia. This study examines the readiness and challenges of implementing VR technology at Yayasan Pendidikan YIMI Gresik, covering KB-TK, SD, and SMP levels. Using surveys, interviews, and field observations, the research assessed infrastructure, training needs, and potential benefits. The survey results show moderate readiness scores across units (KB-TK = 3.1, SD = 3.4, SMP = 3.2 on a 5-point scale), with training needs identified as a critical gap. The findings reveal that while VR has strong potential to enhance administrative efficiency and user satisfaction, its adoption is hindered by limited infrastructure and lack of intensive user training. This study provides one of the first empirical insights into VR readiness for school administration in Indonesia and offers a foundation for future planning and policy in educational management technology.